QUR’ANIC ECONOMIC INTERPRETATION THROUGH A THEMATIC EXEGESIS APPROACH IN DETERMINING THE LEGAL STATUS OF CONTROVERSIAL DROPSHIPPING ON E-ECONOMY PLATFORMS - Mukhtar Yunus (Program Pascasarjana UIN Sumatera Utara, 2025)
The development of electronic commerce in 2025 has given rise to the dropshipping business model, which has become a subject of legal dispute among scholars and practitioners of Islamic economics. This phenomenon raises a fundamental question regarding the legality of digital transactions in which the seller does not possess physical ownership of the goods being traded. This study aims to reconstruct the legal basis of dropshipping through a thematic exegetical approach to economic verses in the Qur’an, while considering the controversies that emerge on contemporary e-economy platforms. The method applied is qualitative research based on library research, using thematic exegesis analysis of mu‘amalah verses, synthesized with the methods of taḥqīq al-manāṭ and istinbāṭī qiyās in Islamic commercial jurisprudence. The findings show that conventional dropshipping practices violate the principle of bay‘ mā lā yamlik and contain gharar fāḥish related to ownership, product specifications, and delivery time. However, through the reconstruction of the contract into wakālah bil ujrah, salam, or samsarah, this model can be accommodated within the framework of Islamic law. The thematic exegetical approach to QS. al-Baqarah [2]: 275, QS. al-Nisā’ [4]: 29, and QS. al-Mumtaḥanah [60]: 8 affirms that economic transactions must fulfill the requirements of contractual clarity, lawful ownership, and information transparency. This study recommends the adoption of the wakālah contract as the most optimal solution because it minimizes the risk of gharar and clarifies the allocation of responsibility (ḍamān) among suppliers, dropshippers, and consumers.